Assessment of microstructural changes in processed products from green peas - A. V. Samoilov; N. M. Suraeva; M. V. Zaytseva (Пищевые системы, 2021)
A demand for canned vegetables and fruit depend, first of all, on their consumer characteristics. These products should correspond to high requirements regarding their nutritional and biological value, as well as sensory properties. The aim of the work was to study the microstructural changes in the cells of green peas in the products of their processing. Fresh, frozen and canned peas made from fresh and rehydrated raw materials were used as objects of the research. Components such as chlorophyll and starch were characterized in the cells of the hypodermis and parenchyma, respectively, using light microscopy. It was found that plastids with chlorophyll stained in the bright green color were present only in cells of the hypodermis of frozen peas. Moreover, the same color of the pigment was also recorded in the samples of fresh peas. Appearance of brown hues in these cells was observed in the canned product from fresh peas, which was associated with transformation of chlorophylls into pheophytins and pyrophephytins. The hypodermis in the samples of canned peas from rehydrated raw materials was represented by almost colorless cells. When analyzing the preparations of the parenchymal cells of the indicated processed products stained with iodine, it was shown that starch grains in the samples of frozen and canned green peas from fresh raw materials maintained their concentric shape, while swelling of starch grains was observed in the stained preparations of the parenchyma of canned peas from rehydrated raw materials. The comparative microstructural analysis of processed products from green peas showed that maximum quality had the frozen product from fresh raw materials as the studied indicators (chlorophyll and starch grains) showed.